The influence of intellectual capital and corporate governance on financial performance of Islamic banks - Rifqi Muhammad; Muhammad Aldino Mangawing; Selfira Salsabilla (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose - This study aims to analyze the effect of intellectual capital, independent directors, academic directors, and sharia supervisory boards on the financial performance of Islamic banks. The selection of samples observation based on the database of Best Islamic Financial Institutions Award, includes Afghanistan, Algeria, Bahrain, Bangladesh, Brunei Darussalam, Egypt, Indonesia, Jordan, Kazakhstan, Kuwait, Lebanon, Malaysia, Maroko, Nigeria, Oman, Pakistan, Palestine, Qatar, Saudi Arabia, Singapore, South Africa, Sri Lanka, Thailand, Tunisia, Turkey, and Uni Emirate Arab. Methodology - This study uses a sample of 20 Islamic banks in several countries which received the "Best Islamic Financial Institutions Award 2018" by Global Finance Magazine and has published financial reports for the period of 2013-2017. This study adopted panel regression analysis and utilized the Random Effect Model.Findings - The results of the study prove that intellectual capital has a positive effect on financial performance. While independent directors, academic directors, and the Sharia Supervisory Board (SSB) have no effect on the financial performance of Islamic banking companies. These results indicate that intellectual capital is a force for Islamic banking to increase company value through financial performance. While the factors related to corporate governance tend to reduce performance due to several limitations for management in carrying out its operational activities.Research limitations – this study has a limitation in using Islamic banking data from various countries with backgrounds that are certainly different from one another which might be bias. Practical implications – This study suggest that management needs to allocate its resources to provide guidance and development of human resources through regular training in the field of fiqh muamalah, contemporary Islamic banking products and services, effective business communication, as well as extensive market knowledge to anticipate the competition in ways that are in accordance with the principles of sharia.Originality – This research fills a research gap in investigating the nexus of intellectual capital and corporate governance mechanism on Islamic banking performance which has not been discussed in previous papers, particularly using Islamic banking in several countries that are committed to develop the Islamic financial industry.